2021
DOI: 10.3389/feduc.2021.683672
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gender on Basic Numerical and Arithmetic Skills: Pilot Data From Third to Ninth Grade for a Large-Scale Online Dyscalculia Screener

Abstract: In this study, we analyzed the development and effects of gender on basic number skills from third to ninth grade in Finland. Because the international comparison studies have shown slightly different developmental trends in mathematical attainment for different language groups in Finland, we added the language of education as a variable in our analysis. Participants were 4,265 students from third to ninth grade in Finland, representing students in two national languages (Finnish, n = 2,833, and Swedish, n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 65 publications
2
15
0
Order By: Relevance
“…All four profiles showed an ascending or stable trend in math performance from the beginning of eighth grade to the end of ninth grade (the final year of compulsory schooling in the Finnish system). Although secondary school is generally linked to downward developmental trends in mathematics performance (Wijsman et al, 2016), performance improved or remained the same in all groups during the two years of our study, which is in concordance with recent Finnish results (Räsänen et al, 2021;Widlund et al, 2021). As parallel versions of the math test were used, the improvement may not be explained by a test-retest effect.…”
Section: Discussionsupporting
confidence: 90%
“…All four profiles showed an ascending or stable trend in math performance from the beginning of eighth grade to the end of ninth grade (the final year of compulsory schooling in the Finnish system). Although secondary school is generally linked to downward developmental trends in mathematics performance (Wijsman et al, 2016), performance improved or remained the same in all groups during the two years of our study, which is in concordance with recent Finnish results (Räsänen et al, 2021;Widlund et al, 2021). As parallel versions of the math test were used, the improvement may not be explained by a test-retest effect.…”
Section: Discussionsupporting
confidence: 90%
“…Similar inconsistent findings are also identified in studies conducted in Finland. For example, recent studies examining the effect of gender on arithmetic fluency skills and have suggested that boys performed better than girls (Räsänen et al, 2021;Torppa et al, 2023), whereas in the TIMSS 2018 study, 15-year-old girls in Finland outperformed boys in curriculumbased mathematics (Vettenranta et al, 2020).…”
Section: Predictors Of Arithmetic Skillsmentioning
confidence: 99%
“…It may be valuable to try to detect those pupils who have real challenges related to dyscalculia or parallel learning disability related to mathematics. Maybe, at some point, some kind of numeracy screening tests such as functional numeracy assessment (Funa) test (see Funa consortium, 2019;Räsänen et al, 2021) could be used in an early phase, and relevant scaffolding techniques and teaching methods could be developed to help these children during the first stages of development of mathematical concepts, procedures, as well as abstraction and thinking-maybe even before the grade 1.…”
Section: Discussionmentioning
confidence: 99%